Focus Groups : Theory and Practice - Stewart, David W. (SAGE Publications, Inc. (US), 2014)
The fully updated Third Edition of Focus Groups: Theory and Practice offers a unique blend of focus group theory and practice in a single, easy-to-read source. It provides systematic treatment to the design, conduct, and interpretation of focus group data within the context of social science research and theory. Known for accessibility and step-by-step guidance, comprehensive treatment, and historical perspective, the book examines every facet of focus group research, from the selection and recruitment of group participants, to the selection of a moderator and conducting of interviews, to the analysis of focus group data. The Third Edition reflects the growing use of focus group research to address an increasingly broad array of issues that have a global span, and also provides more guidance on conducting virtual focus groups.